2003
DOI: 10.2166/ws.2003.0100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorine level on the growth of biofilm in drinking water pipes

Abstract: Three analogous laboratory-scale water pipe systems were constructed to study the effects of three chlorine levels of finished water on the growth of biofilm. The experimental results indicated that the heterotrophic plate counts (HPCs) of biofilm for chlorine-free water were approximately 2 and 3 orders of magnitude higher than those for low-chlorine water (0.3-0.5 mg/l Cl2) and high-chlorine water (1.2-1.5 mg/l Cl2), respectively. The difference in HPCs between low-chlorine water and high-chlorine water was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Even if pathogen density in the water column were low enough that infection of consumers did not occur, uncertainty surrounding the fate of injected pathogens present in the pipe material and biofilm would assuredly reduce the number of people utilizing municipal potable water. Therefore, understanding how long allochthonous pathogens survive in biofilm and/or pipe material under oligotrophic drinking water conditions, and decontamination of that material, is an important research topic.It is well known that biofilm-associated microorganisms survive longer in the presence of disinfectants than planktonic organisms (8,(20)(21)(22)34). However, information on persistence of microbiological agents in water distribution system pipe material is limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even if pathogen density in the water column were low enough that infection of consumers did not occur, uncertainty surrounding the fate of injected pathogens present in the pipe material and biofilm would assuredly reduce the number of people utilizing municipal potable water. Therefore, understanding how long allochthonous pathogens survive in biofilm and/or pipe material under oligotrophic drinking water conditions, and decontamination of that material, is an important research topic.It is well known that biofilm-associated microorganisms survive longer in the presence of disinfectants than planktonic organisms (8,(20)(21)(22)34). However, information on persistence of microbiological agents in water distribution system pipe material is limited.…”
mentioning
confidence: 99%
“…It is well known that biofilm-associated microorganisms survive longer in the presence of disinfectants than planktonic organisms (8,(20)(21)(22)34). However, information on persistence of microbiological agents in water distribution system pipe material is limited.…”
mentioning
confidence: 99%
“…114 It has been found that bacteria grown on iron pipe surface is more resistant to free chlorine compared to that grown in PVC, copper or galvanized surfaces. 33,115 The pipe materials leaching into water through corrosion can also significantly affect the chloramine decay. The effect of pipe materials on chloramine decay largely depends on the water quality and corrosion intensity.…”
Section: Pipe Wall Decaymentioning
confidence: 99%